Kalimat Majemuk dalam Novel Cahaya di Bawah Cahaya Karya Helvy Tiana Rosa, Benny Arnas, dan Asma Nadia - Vadria Nofrianita; Marsis Marsis; Hasnul Fikri; Yetty Morelent; Ineng Naini (Jurnal Ilmiah Pendidikan Scholastic, 2023)
This study discusses how to use compound sentences in the novel â€œCahaya di Bawah Cahayaâ€ by Helvy Tiana Rosa, Benny Arnas, and Asma Nadia. The purpose of this research is to describe the use of compound sentences in the novel. The method used in this research is descriptive qualitative method. The data source for this research is the novel â€œCahaya di Bawah Cahayaâ€ by Helvy Tiana Rosa, Benny Arnas, and Asma Nadia. Based on the results of data analysis found (1) equivalent compound sentences 64, (2) multilevel compound sentences 21, and (3) mixed compound 32.